PENGARUH COVID-19 TERHADAP PROSES PEMBELAJARAN VIRTUAL DI INDONESIA - Ahmad Darmawan; Lesi Hertati; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Indonesian Journal of Thousand Literacies, 2023)
The Covid-19 pandemic that hit almost all countries in the world, including Indonesia, caused tremendous panic for the entire community, as well as devastating all sectors of life. The Indonesian government also adopted a policy that aims to break the chain of transmission of the Covid-19 pandemic. One of them is the application of social distancing policies, where residents must carry out all activities at home, such as working, studying, including carrying out worship. The application of this social distancing policy clearly has a profound impact on all sectors of life, especially the economic sector, which indirectly causes economic slowdowns. Apart from having an impact on the economic sector, the education sector was also hit by a quite fatal impact. Teaching and learning activities have to be done remotely. However, from this policy there are also many parties who are not ready to carry out learning via distance or what is known as online. Readiness still needs to be addressed from distance learning, many people apparently cannot participate in distance learning activities due to the limited ability of the community, many of whom do not have the tools that support distance learning